Detection on ectoparasites on small ruminants and their impact on the tanning industry in Sulaimani province - Bahzad Mustafa (Iraqi Journal of Veterinary Sciences, 2019)
The study was carried out through the clinical examination on the skins of sheep and goats to identify the quality and processed in the tanneries. Parasitic skin diseases caused by ectoparasites such as mange mites, lice, and ticks are among these threats resulting in a serious economic loss to the tanning industry and the country as a whole. Out of 38066 sheep and 9889 goats examined in Sulaimani slaughterhouse in spring season 2017, shows statistically significant P<0.05 between sheep and goats prevalence; 9.35% and 7.43% respectively with one or more ectoparasites. Three different of ectoparasites were infested in both sheep and goats namely; hard tick, lice and mite. Five species of hard tick (Ixodidae) were identified in sheep and goats as follows; Boophilus spp 3.68% and 14.16%, Rhipicephalus sanguineous 12.47% and 28.63%, Rhipicephalus turanicus 7.50% and 15.96%, Hyalomma a. anatolicum 11.90% and 31.30%, Hyalomma marginatum 9.26% and 9.95%) respectively. Two species of lice were identified in sheep namely, Damalinia ovis 17.74% and Linognathus stenopsis 13.63%, and D. caprae 10.97% and L. stenopsis 6.22% on goats. Highly infested were identified with mite on sheep include Psarcoptic scabiei 13.83% and Psoroptic ovies 9.98%, while only one species founded in this study in goats namely, Psarcoptic scabiei 22.79%. The overall number of skins refused to tanning industry 164 (4.61%) in sheep and 116 (15.78%) in goat. The difference in the prevalence of skin disease infestation between refused skin in both sheep and goats were statistically significant in ruminants (P<0.05). This paper deals with major skin defects in occurrence by ectoparasites sheep and goats in Sulaimani province.